Failure of Breathing in Heavy Preeklampsia With Peripartum Cardiomiopathy - Desilia Atikawati; Diyan Ekawati; Pusparini Kusumajati; Prasenohadi Prasenohadi; Menaldi Rasmin (Perhimpunan Dokter Paru Indonesia (PDPI)/The Indonesian Society of Respirology (ISR), 2017)
Physiological alterations during pregnancy generate higher risk of pulmonary edema and acute respiratory failure. Respiratory failure occurs in 0.2% pregnancy, particularly in postpartum period. Respiratory failure can be developed by specific conditions related to pregnancy, such as preeclampsia and peripartum cardiomyopathy. We present the case of 34-year-old female, with 36 weeks of pregnancy, that came with shortness of breath since an hour before admitted. Patient also had vaginal discharge in the last two hours before admitted. Fetal movement was active. Shortness of breath was accompanied with cough. Physical examination revealed hypertension (160/110 mmHg) and rales on both lungs. Blood gas analysis showed severe hypoxemia. Patient were intubated and underwent C-section afterwards. Chest x-ray showed heart enlargement. Echocardiography result showed fraction ejection 25%, global hypokinetic, mild mitral and tricuspid regurgitation, with conclusion of peripartum cardiomyopathy. This case illustrates respiratory failure in severe preeclampsia and peripartum cardiomyopathy. This condition leads to acute pulmonary edema that impairs ventilation/perfusion process. Mechanical ventilation can assure adequate oxygen delivery. Non-invasive ventilation (NIV) is well suited to short-term ventilatory support, and avoids the potential complications of endotracheal intubation and the associated sedation. (J Respir Indo. 2017; 37(4): 325-36)